2005
DOI: 10.2320/matertrans.46.481
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Helium Production and Heat Treatment on Neutron Irradiation Hardening of F82H Steels Irradiated with Neutrons

Abstract: The influcence of addition of 10 B and 11 B on radiation hardening as a function of irradiation temperature was examined in reducedactivation martensitic F82H+B steels (8Cr-2W-0.2V-0.04Ta-0.1C-0.006B). Specimens used were 10 B doped, 10 B+ 11 B doped and 11 B doped F82H steels. Helium concentration produced in the specimens through 10 B(n, ) 7 Li reaction was measured from about 15 to about 330 appm. Radiation hardening of the specimens irradiated at 300 C to 2.3 dpa and 150 C to 1.9 dpa was observed. Incremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…It may be necessary to perform a further investigation on the effect of lithium on DBTT in F82H. In this study, the enhancement of radiation hardening and the shift in DBTT is shown in the F82H steel irradiated at 250°C to 2.3 dpa with helium up to about 330 appm He, however, the enhancement is reduced by increasing irradiation temperature at 300°C [42]. This trend with increasing irradiation temperature matches with previous studies of Shiba and Rieth [5,9].…”
Section: Radiation Embrittlement Due To Helium Productionsupporting
confidence: 90%
“…It may be necessary to perform a further investigation on the effect of lithium on DBTT in F82H. In this study, the enhancement of radiation hardening and the shift in DBTT is shown in the F82H steel irradiated at 250°C to 2.3 dpa with helium up to about 330 appm He, however, the enhancement is reduced by increasing irradiation temperature at 300°C [42]. This trend with increasing irradiation temperature matches with previous studies of Shiba and Rieth [5,9].…”
Section: Radiation Embrittlement Due To Helium Productionsupporting
confidence: 90%
“…However, there was a possibility that the addition of boron or nickel may cause severe irradiation embrittlement. In this experiment, there are no effects of chemical additional element on DBTT [16,17], the shift of DBTT [11], the increment of irradiation hardening [18,19] and defect clusters [20,21] as reported in previous studies. It is therefore concluded that helium production can affect the shift of DBTT.…”
Section: Small Punch Testingsupporting
confidence: 65%
“…These systems are desired to operate at relatively higher temperatures. It is reported that helium atoms can affect DBTT [3][4][5][6][7], swelling behavior [8][9][10][11][12][13][14][15] and irradiation hardening [16][17][18][19][20][21][22][23] in martensitic steels. To study the synergistic effects of displacement damage and helium on mechanical properties and microstructure, there are some specific experimental methods.…”
Section: Introductionmentioning
confidence: 99%